2016
DOI: 10.1152/ajpgi.00355.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 and exercise-induced hepatic mitochondrial adaptations

Abstract: Exercise stimulates hepatic mitochondrial adaptations; however, the mechanisms remain largely unknown. Here we tested whether FGF21 plays an obligatory role in exercise induced hepatic mitochondrial adaptations by testing exercise responses in FGF21 knockout mice. FGF21 knockout (FGF21-KO) and wild-type (WT) mice (11-12 wk of age) had access to voluntary running wheels for exercise (EX) or remained sedentary for 8 wk. FGF21 deficiency resulted in greater body weight, adiposity, serum cholesterol, insulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Thus, mitochondria-related markers were assessed in WAT and BAT to determine the potential impact of loss of FGF21 on the ability of exercise to affect these parameters. Consistent with our previous observation that hepatic mitochondrial function is impaired in FGF21KO mice and almost completely restored by exercise training (Fletcher et al 2016), our current findings revealed important roles of both FGF21 and exercise in mediating adipose tissue mitochondrial adaptations.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, mitochondria-related markers were assessed in WAT and BAT to determine the potential impact of loss of FGF21 on the ability of exercise to affect these parameters. Consistent with our previous observation that hepatic mitochondrial function is impaired in FGF21KO mice and almost completely restored by exercise training (Fletcher et al 2016), our current findings revealed important roles of both FGF21 and exercise in mediating adipose tissue mitochondrial adaptations.…”
Section: Discussionsupporting
confidence: 93%
“…As previously reported (Fletcher et al 2016), no differences existed in running distance between FGF21KO-EX and WT-EX groups, and both groups experienced an increase in energy intake and relative cardiac tissue mass, suggestive of similar training adaptations. However, compared to WT-EX, FGF21KO-EX animals weighed more, had a higher total body fat percentage, and consumed more total energy (Table 1).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…FGF‐2 is one of the most studied FGFs, involved in various endocrine signaling trails, serum phosphate regulation, angiogenesis, wound healing, and embryonic development; additionally, FGF‐2 plays a significant role in the morphogenesis, bone signaling, and cartilage metabolism . Among all these features, FGF‐2 was also shown to (1) influence cell proliferation and stimulate DNA synthesis; (2) mediate the metabolic function of tissues, leading to repair by its releasing from the extracellular matrix (ECM) and regeneration of lost tissues, being used against different cardiovascular disorders; and (3) augment ECM synthesis …”
Section: Introductionmentioning
confidence: 99%